Plan estratégico para la empresa de transporte pesado “Quevetranspe. sa., cantòn Quevedo periodo 2014-2017. - Navas Solis, Nathaly Rocio (2015)
This paper presents the Strategic Plan for Heavy Transport Company SA QUEVETRANSPE Quevedo Canton period 2014-2017. The corporate strategic plan developed here allows aligning objectives based on the provision of quality services, and greater institutional participation, modern management with transparency and efficiency. In the city of Quevedo is the headquarters of the Cooperative Heavy Transport, which has taken the name "QUEVETRANSPE SA, is a cooperative subject to the Act and General Regulations Cooperative limited liability to its share capital and of unlimited duration…..